2021
DOI: 10.3390/ijerph182212089
|View full text |Cite
|
Sign up to set email alerts
|

A One Health Review of Community-Acquired Antimicrobial-Resistant Escherichia coli in India

Abstract: Antimicrobial resistance (AMR) threatens to undermine nearly a century of progress since the first use of antimicrobial compounds. There is an increasing recognition of the links between antimicrobial use and AMR in humans, animals, and the environment (i.e., One Health) and the spread of AMR between these domains and around the globe. This systematic review applies a One Health approach—including humans, animals, and the environment—to characterize AMR in Escherichia coli in India. E. coli is an ideal species… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
5
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 55 publications
0
5
0
Order By: Relevance
“…Intersectoral collaboration happens primarily between human health and animal health scientists, though AMR studies may also involve environmental sampling and/or participation from the environmental sector. In a systematic review of studies from 18 states examining antimicrobial-resistant E. coli across India, only 10% (4 out of 38) conducted interdisciplinary sampling—defined as sampling from a combination of human, animal, or environmental sources ( 19 ). The research studies often feature a multidisciplinary approach, combining social/epidemiological surveys with laboratory-based and/or economic investigations ( Table 1 ).…”
Section: Resultsmentioning
confidence: 99%
“…Intersectoral collaboration happens primarily between human health and animal health scientists, though AMR studies may also involve environmental sampling and/or participation from the environmental sector. In a systematic review of studies from 18 states examining antimicrobial-resistant E. coli across India, only 10% (4 out of 38) conducted interdisciplinary sampling—defined as sampling from a combination of human, animal, or environmental sources ( 19 ). The research studies often feature a multidisciplinary approach, combining social/epidemiological surveys with laboratory-based and/or economic investigations ( Table 1 ).…”
Section: Resultsmentioning
confidence: 99%
“…Globally, antimicrobial resistance has reached an alarming stage leading to a declaration by the World Health Organization (WHO) as one of the most critical threats confronting human health. 1 Recently, the spread of resistance genes has become a public health concern particularly among members of Enterobacteriaceae, with most of the cases reported are due to Escherichia coli, as causes of both community and hospital acquired infections 2 such as gastrointestinal tract infection, wound infection, sepsis, neonatal meningitis, and mainly urinary tract infections (UTI). 3 Besides its causation of multiple infections, E. coli is becoming an increasingly antimicrobial resistant.…”
Section: Introductionmentioning
confidence: 99%
“…On the other side, many E. coli strains have different virulence genes that allow such strains to induce intestinal and extraintestinal infections, both community- and hospital-acquired ( Rajagopal et al, 2021 ). Research has shown that APEC (O1, O2, and O18 serogroups) could be zoonotic pathogens that spread from animals to humans through food and result in extraintestinal infections ( Mellata, 2013 ; Markland et al, 2015 ).…”
Section: Introductionmentioning
confidence: 99%